EvalMax as an alternative to learning assessment and comprehensive training - Maila Velasco, Adriana Paola; Sánchez Manosalvas, Olga Teresa; Rincón López, Víctor Raúl (SATHIRI, 2022)
Evaluation in the school system is still an unsolved problem at the secondary level (primary, higher education, and unified general baccalaureate) of the educational institutions of Ecuador. The Ministry of Education regulates students evaluation and promotion. Although the educational model speaks of evaluation by results or achievements of learning. The practice relies on a traditional evaluative approach and quantitative approach without being able to determine individual results. This problem leads to the action research applied as a case study for an educational software called EvalMAX. This method was implemented as an innovative methodology for the evaluation of learning. This led to identifying the level of individualized achievement and at the same time, the comprehensive training of the students. The research followed a mixed approach, with a quasi-experimental design, it was applied to a predetermined group of high school students and a control group. The application of EvalMAX allowed visualizing a performance improvement, raising the individual and group average in terms of the development and scope of skills with performance criteria, established as desired minimums.
Keywords: Learning assessment; EvalMAX; Comprehensive training; Unified General Baccalaureate